Endoscopic biliary drainage for distal bile duct obstruction due to pancreatic cancer - Masahiro Itonaga; Masayuki Kitano (Clinical Endoscopy)
Approximately 60% of pancreatic cancers occur in the pancreatic head and may present as obstructive jaundice due to bile duct invasion. Obstructive jaundice often leads to poor general conditions and acute cholangitis, interfering with surgery and chemotherapy and requiring biliary drainage. The first choice of treatment for biliary drainage is the endoscopic transpapillary approach. In unresectable tumors, self-expandable metal stents (SEMSs) are most commonly used and are classified into uncovered and covered SEMSs. Recently, antireflux metal stents and large- or small-diameter SEMSs have become commercially available, and their usefulness has been reported. Plastic stents are infrequently used in patients with resectable biliary obstruction; however, owing to the recent trend in preoperative chemotherapy, SEMSs are frequently used because of the long time to recurrent biliary obstruction. Endoscopic ultrasound-guided biliary drainage (EUS-BD) is often performed in patients who are not eligible for the transpapillary approach, and favorable outcomes have been reported. Different EUS-BD techniques and specialized stents have been developed and can be safely used in high-volume centers. The indications for EUS-BD are expected to further expand in the future.